Intersubject correlations in reward and mentalizing brain circuits separately predict persuasiveness of two types of ISIS video propaganda - Cohen, Michael S.; Leong, Yuan Chang; Ruby, Keven; Pape, Robert A.; Decety, Jean (Scientific reports, 2024)
The Islamist group ISIS has been particularly successful at recruiting Westerners as terrorists. A hypothesized explanation is their simultaneous use of two types of propaganda: Heroic narratives, emphasizing individual glory, alongside Social narratives, which emphasize oppression against Islamic communities. In the current study, functional MRI was used to measure brain responses to short ISIS propaganda videos distributed online. Participants were shown 4 Heroic and 4 Social videos categorized as such by another independent group of subjects. Persuasiveness was measured using post-scan predictions of recruitment effectiveness. Inter-subject correlation (ISC) was used to measure commonality of brain activity time courses across individuals. ISCs in ventral striatum predicted rated persuasiveness for Heroic videos, while ISCs in mentalizing and default networks, especially in dmPFC, predicted rated persuasiveness for Social videos. This work builds on past findings that engagement of the reward circuit and of mentalizing brain regions predicts preferences and persuasion. The observed dissociation as a function of stimulus type is novel, as is the finding that intersubject synchrony in ventral striatum predicts rated persuasiveness. These exploratory results identify possible neural mechanisms by which political extremists successfully recruit prospective members and specifically support the hypothesized distinction between Heroic and Social narratives for ISIS propaganda.